Effects of Standard vs Energy‐Dense Formulae on Gastric Retention, Energy Delivery, and Glycemia in Critically Ill Patients. Issue 4 (18th February 2021) - Chapple, Lee‐anne S.; Summers, Matthew J.; Weinel, Luke M.; Abdelhamid, Yasmine Ali; Kar, Palash; Hatzinikolas, Seva; Calnan, Deborah; Bills, Madison; Lange, Kylie; Poole, Alexis; O'Connor, Stephanie N.; Horowitz, Michael; et al.
Abstract: Background: Energy‐dense formulae are often provided to critically ill patients with enteral feed intolerance with the aim of increasing energy delivery, yet the effect on gastric emptying is unknown. The rate of gastric emptying of a standard compared with an energy‐dense formula was quantified in critically ill patients. Methods: Mechanically ventilated adults were randomized to receive radiolabeled intragastric infusions of 200 mL standard (1 kcal/mL) or 100 mL energy‐dense (2 kcal/mL) enteral formulae on consecutive days in this noninferiority, blinded, crossover trial. The primary outcome was scintigraphic measurement of gastric retention (percentage at 120 minutes). Other measures included area under the curve (AUC) for gastric retention and intestinal energy delivery (calculated from gastric retention of formulae over time), blood glucose (peak and AUC), and intestinal glucose absorption (using 3‐O‐methyl‐D‐gluco‐pyranose [3‐OMG] concentrations). Comparisons were undertaken using paired mixed‐effects models. Data presented are mean ± SE. Results: Eighteen patients were studied (male/female, 14:4; age, 55.2 ± 5.3 years). Gastric retention at 120 minutes was greater with the energy‐dense formula (standard, 17.0 ± 5.9 vs energy‐dense, 32.5 ± 7.1; difference, 12.7% [90% confidence interval, 0.8%–30.1%]). Energy delivery (AUC120, 13, 038 ± 1119 vs 9763 ± 1346 kcal/120 minutes; P = 0.057), glucose control (peak glucose, 10.1 ± 0.3 vs 9.7 ± 0.3 mmol/L, P = 0.362; and glucose AUC120 8.7 ± 0.3 vs 8.5 ± 0.3 mmol/L.120 minutes, P = 0.661), and absorption (3‐OMG AUC120, 38.5 ± 4.0 vs 35.7 ± 4.0 mmol/L.120 minutes; P = .508) were not improved with the energy‐dense formula. Conclusion: In critical illness, administration of an energy‐dense formula does not reduce gastric retention, increase energy delivery to the small intestine, or improve glucose absorption or glucose control; instead, there is a signal for delayed gastric emptying.